On-farm Phenotypic Characterization of Indigenous Goat Types in Selected Districts of South Gondar Zone, North Western Ethiopia - Hareri, Michael Abera; Kagne, Habtamu; Alemayehu, Kefyalew (Archives of Veterinary Science, 2025)
This study aimed to gather basic information on phenotypic characteristics and develop live weight estimation equations based on body measurements of indigenous goat types in selected districts of the South Gondar Zone. Multistage purposive sampling was employed based on the potential of goat production. For generating quantitative and qualitative data, linear body measurements were taken from 630 mature goats. Dentition was used to estimate the age of goats as age group one (1PPI), age group two (2PPI), and age group three (3PPI). Data were gathered through field observations and linear body measurements of sampled populations. The most frequently observed coat colors were white (23.80%), white and red (18.57%), red (13.70%), gray (13.17%), brown (9.50%), and black (6.03%). Moreover, the most frequently observed coat color patterns of the sampled goat population in the study area were plain (65.1%), followed by patchy (25.2%) and spotted (9.7%). Sex of animals affected (P<0.05) body weight and all of the body measurements except for ear length and tail length. The animals’ location difference affected all body measurements (P < 0.05), except for heart girth. The age of animals contributed significantly to differences in body weight and all linear body measurements. The correlation coefficient was consistently highest between body weight and chest girth in males (r = 0.90) and females (r = 0.83). Multiple regression analysis revealed that Chest girth was the most crucial trait in predicting body weight. There was no standard weighing balance for selling live animals at reasonable prices.